Light Elements in the Universe - Randich, Sofia; Magrini, Laura (Frontiers in Astronomy and Space Sciences, 2021)
Due to their production sites, as well as to how they are processed and destroyed in stars, the light elements are excellent tools to investigate a number of crucial issues in modern astrophysics: from stellar structure and non-standard processes at work in stellar interiors, to age dating of stars; from pre-main sequence evolution, to the star formation histories of young clusters and associations, to the issue of multiple populations in globular clusters; from Big Bang nucleosynthesis, to the formation and chemical enrichment history of the Milky Way galaxy and its populations, just to cite some examples. In this paper, we focus on lithium, beryllium and boron (LiBeB) and on carbon, nitrogen, and oxygen (CNO). LiBeB are rare elements, with negligible abundances with respect to hydrogen; viceversa, CNO are among the most abundant elements in the Universe, after H and He. Pioneering observations of light-element surface abundances in stars started almost 70 years ago and huge progress has been achieved since then. Indeed, whilst, for different reasons, precise measurements of LiBeB and CNO are difficult, even in our Sun, the advent of state-of-the-art ground- and space-based instrumentation has allowed the determination of high-quality abundances in stars of different type and belonging to different Galactic populations, from metal-poor halo stars to young stars in the solar vicinity, from massive stars to cool dwarfs and giants. Noticeably, with the recent advent of large spectroscopic surveys performed with multi-fiber spectrographs, detailed and homogeneous information on the abundances of Li and CNO for statistically significant samples of stars has been acquired, allowing us to obtain new results and insights and, at the same time, opening new questions and challenges. A complete understanding of the light-element patterns and evolution in the Universe has not been still achieved. Perspectives for further progress will open up soon thanks to the new generation instrumentation that is under development and will come on-line in the coming years.